PENGGUNAAN MEDIA THE MAGICAL MAP OF MAJALENGKA UNTUK MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN MEMBACA PETA - Rohaeni, Ina; Hanifah, Nurdinah; Sudin, Ali (Jurnal Pena Ilmiah, 2017)
This research based on menial result learning in the subject of elements of the local environmental map caused by the optimalize media used is less. The subjects of this research was 48 students of fourth grade Rancaputat Elementary School. The purpose of this research was to increasing result learning and reading map skills. The method research was used the classrom action research with the spiral design by Kemmis and Taggart, the steps were planning, immplementation, observation, and reflection. The immplementationsteps used up to three cycles. Result learning improved, the first cycles (41,67%), the second cycles (56,25%), the third cycles (89,58%) and reading map skills up to the third cycles reached (89,58%). The conclusion was the magical map media of Majalengka increased the result learning and reading map skills of reading environtment map components.